THE LEGAL CONSIDERATIONS OF UMAR IBN AL-KHATTAB AND THEIR RELEVANCE TO THE APPLICATION OF AMNESTY AND ABOLITION IN CRIMINAL LAW IN INDONESIA - Mawardi, Mawardi; Putra, Firman Surya; Cheha, Muhammad Zakee (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Umar Bin Khattab was the Caliph who succeeded Abu Bakr Shiddiq. He was famous for his numerous and brilliant Ijtihad, so he was also known as the pioneer of Ahl Ra'yu in ijtihad among the companions. This study aims to reveal Umar's ijtihad models in implementing Islamic Law during his leadership, more specifically to his relatively new decisions, which had never been implemented by the Prophet Muhammad and Abu Bakr before. This study uses a qualitative research method with a library research approach or literature study. This method aims to explore, analyze, and synthesize various literatures relevant to the theme of the history of the development and renewal of Islamic law. The main data sources used in this study are books, scientific journals, articles, and other documents that discuss aspects of the development of Islamic law during the time of Umar bin Khattab. In addition, this study also utilizes the works of contemporary Islamic thinkers who provide new perspectives on the renewal of Islamic law. This article will describe the transformation Umar ibn Khattab undertook in the implementation of Islamic law during his time. In addition to utilizing the Quran and Hadith, Umar also utilized reason as a method for enforcing Islamic law’s and is relevant to the implementation of law in Indonesia in the form of the implementation of amnesty and abolition for prisoners.